Investigating Composting as a Mitigation Strategy for Climate Change Using a Modelling Approach - Ramasamy Coolen, Preeya Vijayalakshmee; Makoondlall-Chadee, Toshima; Bokhoree, Chandradeo; Foogooa, Ravi (European Journal of Sustainable Development, 2021)
The waste management sector accounts for 19% of greenhouse gases produced by the island of Mauritius, and is second to the energy sector which contributes about 77% of total emissions. Significant mitigating measures are being sought to reduce the impact of the waste sector. The main greenhouse gas produced from waste in Mauritius is methane from landfill disposal. Among the different alternate waste management scenarios proposed, home composting is one strategy to achieve carbon reductions in the sector. However, this target can only be achieved if the composting process is properly controlled. Objectively, a lumped parameter model was used to analyse the set of variation parameters to achieve greatest reduction in methane through optimal composting. The composting matrix was modelled as a point source. Mass balance equations were coupled with heat transport equations and reaction kinetics equations to determine the optimal set of parameters for efficient composting of yard waste and kitchen waste. The simulations demonstrated that bulking of vegetable waste prior to composting is required to prevent production of methane.